2018
DOI: 10.1007/s00384-018-3015-9
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of outpatient treatment for acute diverticulitis

Abstract: BackgroundThe shift from routine antibiotics towards omitting antibiotics for uncomplicated acute diverticulitis opens up the possibility for outpatient instead of inpatient treatment, potentially reducing the burden of one of the most common gastrointestinal diseases in the Western world.PurposeAssessing the safety and cost savings of outpatient treatment in acute colonic diverticulitis.MethodsPubMed and EMBASE were searched for studies on outpatient treatment of colonic diverticulitis, confirmed with compute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 42 publications
(71 reference statements)
0
30
0
6
Order By: Relevance
“…Two recent systematic reviews [93,94] have studied the evidence. One included 21 and the other 19 studies including one randomized trial [95] comparing inpatient and outpatient treatment for patients with uncomplicated diverticulitis, and comparable rates of readmission were found.…”
Section: Which Group Of Diverticulitis Patients Can Safely Be Treatedmentioning
confidence: 99%
“…Two recent systematic reviews [93,94] have studied the evidence. One included 21 and the other 19 studies including one randomized trial [95] comparing inpatient and outpatient treatment for patients with uncomplicated diverticulitis, and comparable rates of readmission were found.…”
Section: Which Group Of Diverticulitis Patients Can Safely Be Treatedmentioning
confidence: 99%
“…According to this theory, the role of bacterial overgrowth appears to be prominent, so that antibiotic therapy is actually considered the cornerstone therapy for acute diverticulitis. However, in the last decade, various studies have shown that acute uncomplicated diverticulitis may be safely managed without standard antibiotic therapy, at least in selected patients [ 10 ]. However, further long-term, randomized clinical trials will be required before we change our clinical practice.…”
mentioning
confidence: 99%
“…Several studies have shown outpatient treatment to be safe for the treatment of mild disease in the absence of significant comorbidity, and where the patient is able to tolerate oral diet and antibiotics. 19,20 Isacson et al were able to demonstrate cost savings after their institution adopted a policy of selective outpatient management. Their total healthcare cost related to diverticulitis was Euro 558 679 in 2011 (preimplementation of outpatient policy) compared with Euro 370 370 in 2014 (P < 0.001).…”
Section: Discussionmentioning
confidence: 99%